(untitled) (Archives of Pediatrics of Uruguay, 2023)
Mounier Kühn syndrome is a rare airway pathology characterized by abnormal dilatation of the trachea and bronchi. It should be suspected in the presence of recurrent bronchopulmonary infections and tracheobronchial irritation. The diagnosis is made by measuring the tracheal diameter in three segments of its anatomy, through thoracic tomography. We present the case of a 10 year-old male school boy with a history of recurrent respiratory infections, hospitalized for a pneumonic condition; the findings reported in the thoracic tomography correspond to a tracheobronchomegaly in addition to an increase of the esophageal diameter. The treatment of this entity is symptomatic with supportive measures and pulmonary physical therapy.